Building Trust for Enhanced Job Satisfaction: Insights from High School Teachers in Pekanbaru City - Nurfaisal Nurfaisal; Sunengko Sunengko (STAI Hubbulwathan Duri, 2023)
This study aims to investigate the level of job satisfaction among public high school teachers in Pekanbaru City through the lens of teacher trust. Using a survey method with a causal approach, the research examines a sample of 200 teachers, selected via simple random sampling, and includes a pilot test with 40 teachers for method refinement. The study centers on educators in state high schools across Pekanbaru City. Data collection involves a carefully designed questionnaire, validated through Pearson Product-Moment correlation and assessed for reliability using Cronbach's Alpha formula. The study reveals a direct and positive correlation between trust and job satisfaction, underscoring the potential to enhance job satisfaction by nurturing higher levels of trust. The findings contribute valuable insights to the education field, suggesting that cultivating trust can positively impact both teacher job satisfaction and overall educational quality. This research sheds light on the interplay between trust and job satisfaction, offering implications for educational institutions and policymakers to create more conducive teaching environments and elevate the educational experience for both teachers and students.